Profiling the high frequency wine consumer by price segmentation in the US market - Liz Thach; Janeen E. Olsen (Wine Economics and Policy, 2015)
Heavy users of consumer products are important to marketers as a profitable target segment. This is equally true in the wine industry, but with the added precaution of encouraging responsible consumption. This study examines the attributes and behaviors of 681 high frequency (heavy-user) wine consumers in the US, based on a price segmentation of High, Moderate, and Low Spenders. For this study, price segmentation was defined as the price typically paid for a bottle of wine for home consumption. Significant differences were discovered based on gender, age, income, wine involvement, shopping channel, ecommerce/social media usage and other key areas. Implications for marketing managers as well as areas of future research are described.
Keywords: 330; Consumer behavior; Heavy users; Price segmentation; Wine